The Content of the Right to Internet Access - Alvarez, Clara-Luz; Soberanes Diez, Jose Maria (Law, State and Telecommunications Review, 2023)
[Purpose] Having internet access is essential for the full enjoyment of many human rights. Therefore, this Article aims to determine the minimum essential content of the right to the internet in order to both understand the extent to which it deserves protection and to verify compliance with the obligations it entails. We describe the evolving nature of internet and broadband access due to technological developments and social needs. We also present the different positions regarding internet access as a human right or not, as well as how this right is acknowledged in the Mexican Constitution. [Methodology/Approach/Design] The methodology was the review and analysis of norms, case law, academic and public policy documents, as well as references to relevant statistical data. The scope of the paper is framed in the discussion of fundamental and human rights. [Findings] The right to internet access has both a negative dimension and a positive one. The negative dimension consists of a State obligation not to limit or restrict the right to internet access. The positive dimension must be determined using the economic, social, and cultural rights standard of the four As, namely, availability, accessibility, acceptability, and adaptability. Finally, we propose the minimum essential content of the right to internet access on those four characteristics. [Practical Implications] - This Article provides arguments and bases for the minimum essential content of the right to internet access and broadband which are relevant for policymakers, judicial decisions, and civil society. Also, the academic debate is and will be open on the subject matter of this paper insofar as the evolutionary nature of technology, demands a constant review and update of the minimum essential content of the right. [Originality/Value] There is currently no literature regarding what a right to internet access and broadband would include as obligations to States and other parties.